KONSEP WAHYU DALAM ALQURAN (KAJIAN SEMANTIK) - Muammar, Arief (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2017)
For prophets who are at a lower level, angels descending to them both in the conscious or dream world, will dwell in their imaginary power and the supernatural nature (revelation) which descends from the Hadhrat miah Scientific will reach their hearts. But for the Prophets who have a position higher than q uqul and angels, the delivery of revelation and the descent and descent of angels will be realized with the permission of the Nafs Nabawi. They can witness and dialogue directly with the angels especially with the angel Jibril witnessed in âthe nature of uqulâ with the form of "Tamatsul Aqli", in the Muslim world with the form "Tamatsul Mitsâli" and in the material world with the form "Tamatsul Nâsuti" and in this way they take revelations from angels